Radiocarbon Dating Historical Mortars: Lime Lumps and/or Binder Carbonate?. Issue 3 (6th April 2018) - Lindroos, Alf; Ringbom, Åsa; Heinemeier, Jan; Hodgins, Greg; Sonck-Koota, Pia; Sjöberg, Pia; Lancaster, Lynne; Kaisti, Riikka; Brock, Fiona; Ranta, Heikki; Caroselli, Marta; Lugli, Stefano
ABSTRACT: Lime lumps and bulk mortars show different 14 C contamination when analyzed in several CO2 fractions isolated from the effervescence of an ongoing hydrolysis reaction. Age profiles of both materials are therefore highly complementary and together they can provide a reliable date. Furthermore, they can also reveal the complexity of the radiocarbon ( 14 C) distribution within the mortar and thus prevent over-interpretation of the data. The lime lump versus bulk mortar dating data presented here has been collected over 22 years, with only a small fraction of the results so far published internationally. Since there has been an increasing interest in mortar dating over recent years with a special focus on lime lumps, and since many laboratories have just begun mortar dating experiments, we wish to present some of the extensive data that already exist. Previously published data from 15 lime lumps (including 34 14 C measurements from sequential dissolution) and 43 new 14 C measurements from 17 lime lumps are presented here. The samples are from medieval Finland and Sweden, classical Rome and medieval Italy, and the Roman Jerash (Gerasa), Jordan.